End-to-End Encryption Security Method - Rahmayani, Rahmayani; yusdartono, Habib Muharry (Cattleya Darmaya Fortuna, 2024)
Crimes such as wiretapping, data theft and other criminal acts in social media, especially in short messages are increasingly common. Several short message service companies are beginning to understand this and continue to strive to advance security features that can protect user data and privacy. One of these efforts is the development of an end-to-end encryption security method. In this article, the author hopes to be able to explain and provide a good understanding of this security method. So that it can be understood by the reader well.